Ultrasound of congenital fetal anomalies : differential diagnosis and prognostic indicators - Paladini, Dario; Volpe, Paolo (New York : Informa Healthcare, 2008)
"An acclaimed overview of ultrasound for the prenatal diagnosis of congenital anomalies returns in a new enlarged edition. In particular, the coverage of both Central Nervous System congenital and acquired anomalies as well as Congenital Heart Disease has been expanded enormously, to make this an impressive comprehensive resource for Fetal Neurology and Fetal Cardiology. Together with additional new chapters on guidelines and protocols, equipment, and disorders of sexual differentiation, and new insight into fetal surgery procedures, this third edition almost becomes three books in one"--
Fetal development and congenital anomalies. First trimester sonographic examination and three-dimensional ultrasound evaluation -- Guidelines and screening protocols -- Equipment, transducers and set-up -- Central and peripheral nervous system : neurosonography and anomalies -- Face and neck anomalies -- the lymphatic system and lymphatic anomalies -- Fetal heart, fetal echocardiography and congenital heart disease -- Thoracic anomalies -- Gastro-intestinal anomalies -- Urinary tract anomalies -- Disorders of sexual differentiation (DSD) -- Skeletal dysplasias and muscular anomalies : a diagnostic algorithm -- Syndromic conditions -- Fetal infections -- Ultrasound in multiple pregnancy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Fetus -- abnormalities; Ultrasonography, Prenatal; Diagnosis, Differential; Congenital Abnormalities -- diagnostic imaging; Fetal Diseases -- diagnostic imaging; Prenatal Injuries -- diagnostic imaging